Bioaugmentation Potential Investigation Using a Phenol Affinity Analysis of Three Acinetobacter Strains in a Multi-Carbon-Source Condition - Fikó, Dezső-Róbert; Ráduly, Botond; Máthé, István; Felföldi, Tamás; Lányi, Szabolcs; Szilveszter, Szabolcs (Water (Basel), 2023)
Bioaugmentation potential and phenol substrate affinity in a multi-carbon-source condition for three Acinetobacter strains (Acinetobacter towneri CFII-87, Acinetobacter johnsonii CFII-99A and Acinetobacter sp. CFII-98) were demonstrated. First, the phenol biodegradation ability of the strains was analyzed in batch experiments with phenol as the sole carbon source. All strains degraded phenol at 100 and 500 mg·L−1 initial concentrations; the maximum specific growth rates were 0.59 and 0.30 d−1 for A. towneri CFII-87, 0.50 and 0.20 d−1 for A. johnsonii CFII-99A, and 0.64 and 0.29 d−1 for A. sp. CFII-98, respectively. For the two tested phenol concentrations, no lag phase was observed for the A. towneri CFII-87 strain, A. sp. CFII-98 presented 4 h and 8 h lag phase, while A. johnsonii CFII-99A presented 3 h and 12 h lag phases. Phenol carbon source dependency of the strains was tested in a multi-carbon-source condition (on phenol-rich synthetic wastewater), both for individual strains and for a consortium prepared as an equal mixture of the three strains. The strains A. towneri CFII-87 and A. sp. CFII-98 and the consortia degraded phenol in 16 h while there was no other significant carbon source consumption during the 48 h trial, as shown by the constant non-phenolic residual chemical oxygen demand (COD) and volatile suspended solids (VSS) concentration after the depletion of phenol. The strain A. johnsonii CFII-99A, however, consumed phenol within 24 h and a further decrease in non-phenolic COD and increase in biomass was also observed upon the depletion of phenol. The highest specific phenol removal rate of 282.11 mg phenol·g VSS∙h−1 was observed in the case of the strain A. towneri CFII-87, followed by A. sp. CFII-98, the consortium and A. johnsonii CFII-99A with 178.84, 146.76 and 141.01 mg phenol·g VSS∙h−1, respectively. Two bacterial strains (A. towneri CFII-87, A. sp. CFII-98) presented a strong affinity to phenol, utilizing it as a primary carbon source, and thus, their use in the bioaugmentation of wastewater bioreactors indicated the viable potential to increase the phenol removal rate of these systems.